Inovasi dan Pengembangan Potensi Masyarakat Melalui Olahan dan Pemasaran Udang di Desa Tanjung Rejo Kecamatan Percut Sei Tuan : Teori Community Organization/Community Developmen - Mayang Febi Awaliah; Natal Fernando Panjaitan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This project research aims to explain the COCD concept for innovation and development provided to village communities in Tanjung Rejo. The method we used was interviews and direct observation in Tanjung Rejo village. The technique we use is direct data analysis and in-depth observation regarding the conditions of the village we want to empower. The results of this research show that the results of the innovation carried out are very influential and have a sustainable impact on the income of local residents as well as exploring the potential and abilities of local residents to be even better than before regarding shrimp food from their shrimp ponds. Based on the results and discussion of the research "Innovation and Development of Community Potential through Shrimp Processing and Marketing in Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency. 1). The applied COCD concepts and theories enable the development of relevant and sustainable solutions, as well as increasing community participation. 2) COCD Concepts and Theory help increase efficiency, improve skills and open up new opportunities, especially opportunities in shrimp innovation which can be a means of developing COCD Concepts and Theory which can help improve the social and economic welfare of the community and create independence for the community.